EFEKTIVITAS PEMBELAJARAN DARING PADA MAHASISWA PRODI BIOLOGI, MATEMATIKA DAN TEKNOLOGI INFORMASI UNIMOR DI BENTANG ALAM LAHAN KERING - Willem Amu Blegur; Krisantus Jumarto Tey Seran; Fried Markus Allung Blegur (Saintek Lahan Kering, 2021)
Pandemic Covid-19 have changed so many aspects in our lives including educational activities. Universitas Timor located in land arid area then influenced by it, in Biology, Information Technology and Maths students in versa. The aims of these research were to study about effecitivity in online learning implementation according to the students and lecturers and to study more what is the barriers and / or supports for the apply in three study program. Data collected using quetionnaires by filling google forms and interview to our respondents. They were students from Biology: 24, Information Technology: 83, Maths: 31 and lecturers: 9. The results performed that our respondents agreed to this implementation while avoiding Covid-19 spread among students and lecturers (Biology: 23, IT: 81, Maths: 30 and lecturers 9 people). Our students spent their own money from their parents to buy intenet debt majority around Rp50.000 - Rp100.000 in a moth (Biology: 12, IT: 47, Maths: 15). The students chosen googleclassroom, googlemeeting, zoommeeing, WAG and combine among them, respectively. Our lecturers and students still could do practices using less resources of laboratory and tools (Biology: 23, IT: 75, Maths: 21). And then the process still gave more progress to the students for their marks and knowledge accoding to them (Biology: 14, IT: 45, Maths: 20). To honest that the students more like to study face to face in class especially Biology and Maths students but neither for IT students.